Inequality Perceptions, Distributional Norms, and Redistributive Preferences in East and West Germany - Andreas Kuhn (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
This paper studies differences in inequality perceptions, distributional norms, and redistributive preferences between East and West Germany. As expected, there are substantial differences with respect to all three of these measures. Surprisingly, however, differences in distributional norms are much smaller than differences with respect to inequality perceptions or redistributive preferences. Nonetheless, individuals from East Germany tend to be more supportive of state redistribution and progressive taxation, and less likely to have a conservative political orientation, even conditional on having the same inequality perceptions and distributional norms.
Keywords: D31; D63; H50; J31; 330; subjective inequality indices; redistributive preferences; political preferences